2018
DOI: 10.1080/1062936x.2018.1497702
|View full text |Cite
|
Sign up to set email alerts
|

A large comparison of integrated SAR/QSAR models of the Ames test for mutagenicity$

Abstract: Results from the Ames test are the first outcome considered to assess the possible mutagenicity of substances. Many QSAR models and structural alerts are available to predict this endpoint. From a regulatory point of view, the recommendation from international authorities is to consider the predictions of more than one model and to combine results in order to develop conclusions about the mutagenicity risk posed by chemicals. However, the results of those models are often conflicting, and the existing inconsis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…Value 0 indicate ames negative while value 1 indicates ames positive. (Benfenati et al, 2018) Highest ames positive probability was found for nos83 while the lowest possibility for nos41.…”
Section: Toxicity Properties Of Top-six Noscapinesmentioning
confidence: 90%
“…Value 0 indicate ames negative while value 1 indicates ames positive. (Benfenati et al, 2018) Highest ames positive probability was found for nos83 while the lowest possibility for nos41.…”
Section: Toxicity Properties Of Top-six Noscapinesmentioning
confidence: 90%
“…available for IAS) or in silico predictions using both (Quantitative) Structure Activity Relationships (QSARs) and grouping/read across (Schilter et al 2014). There are a number of models capable of predicting Ames mutagenicity with high accuracy (Benfenati et al 2018;Honma et al 2019). To increase confidence, it is recommended to integrate QSAR models based on numerical descriptors with rule-based expert systems.…”
Section: Data Interpretationmentioning
confidence: 99%
“…Benfenati et al. (2018) have used deep learning to find a good accuracy of Ames test for mutagenicity, from simple SMILES notation of the chemicals, and similarly, SMILES representation was used by Hirohara et al. (2018) to develop the convolutional neural network for TOX 21.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2019) compared the performance of the prediction of deep neural network (DNN) algorithm models and RF models developed through structural and physicochemical features of chemicals for human ether-ago-go-related gene (hERG) activity. Benfenati et al (2018) have used deep learning to find a good accuracy of Ames test for mutagenicity, from simple SMILES notation of the chemicals, and similarly, SMILES representation was used by Hirohara et al (2018) to develop the convolutional neural network for TOX 21.…”
mentioning
confidence: 99%